The specificity of the development of the secondary education for youth and adults in the province of Buenos Aires in recent history (Estudios Sociales, 2024)
The article analyzes the existence of particular features in the evolution of secondary education for youth and adults in the province of Buenos Aires during recent history. To this end, from a quantitative methodology, various indicators are explored in a comparative manner between the jurisdiction and the rest of the national territory. The main source is the annual educational surveys carried out by the National Ministry of Education, complementing them with other official data referring to certain educational completion programs. As a central argument, it is stated that during the last decades the middle school for this segment of the population has expanded in line with what is happening at the national level, although in the jurisdiction studied said growth has been deployed largely through non-traditional offers, while it has implied a loss of relative weight in favor of other jurisdictions.
Keywords: Secondary education - Education for youth and adults – Province of Buenos Aires – Quantitative Methodology – Educational statistics.